MENINGKATKAN KEPUTUSAN PEMBELIAN MELALUI KUALITAS PELAYANAN DAN PROMOSI PENJUALAN - Aang Curatman; Soesanty Maulany; Shofiullah Shofiullah (Monex: Journal of Accounting Research, 2021)
The purpose of this study is to analyze the effect of service quality and sales promotion on consumer purchasing decisions at E Sport Cirebon Shop, either partially or simultaneously. The population of this research is consumers of E Sport Cirebon stores with unknown population, while the sample is 96 respondents. The sampling technique used non-probability sampling using incidental sampling. This research is an associative type with quantitative methods. Based on the T test it is known that service quality and sales promotion have a partial effect on purchasing decisions, as well as based on the F test it is known that service quality and sales promotion have a simultaneous influence on purchasing decisions. Therefore the company should improve service quality and provide variations in the types of sales promotions to improve consumer purchasing decisions.